Recalcitrant Leg Ulcers as the Only Manifestation of Essential Type 2 Cryoglobulinemia - Brasileiro, A (2013)
Chronic leg ulcers are persistent conditions that might be a diagnostic and therapeutic challenge, with great impact in health care costs and patients’ quality of life. We report a case of a 60-year-old woman, with long-lasting recalcitrant leg ulcers, which led to left leg amputation 10 years ago. Several attempts to heal the right leg were made, including skin grafting in three different occasions and several surgical debridements, all with unsatisfactory outcome. Some months before the ulcers began, the patient had been diagnosed with undifferentiated connective tissue disease because of arthralgia and positive antinuclear antibodies, therefore low dose systemic corticosteroids and azathioprine were prescribed. For the last 4 years she has been followed in our department and since then no evidence of clinical or laboratorial criteria for autoimmune diseases was found, thus the immunosuppressive therapy was stopped. She maintained ever since a high rheumatoid factor but without other evidence of autoimmune disease. Medical history was otherwise irrelevant. Several cutaneous biopsies were performed, with no evidence of malignancy or vasculitis. Recently, cryoglobulins became positive, with type 2b cryoglobulin identification on immunofluorescence. Serology for Hepatitis C virus was consistently negative, hence an Essential type 2 Cryoglobulinemia diagnosis was established. No renal impairment, vascular purpura, arthralgia or arthritis was found. The authors emphasize the importance of considering less common etiologies for chronic leg wounds, even in the absence of other suggestive symptomatology, as well as the pertinence of reconsidering diagnosis in highly suspect cases.